2021
DOI: 10.1186/s12931-021-01809-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic outcomes in patients with haemoptysis

Abstract: Background Haemoptysis is a challenging symptom that can be associated with potentially life-threatening medical conditions. Follow-up is key in these patients to promptly detect new or misdiagnosed pathologic findings. Few prospective studies have evaluated long-term prognostic outcomes in patients with haemoptysis. Furthermore, the role played by antiplatelet and anticoagulant drugs on mortality and recurrence rates is unclear. The aim of this study was to assess mortality after 18 months of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In our study, the most common recurrence risk was seen in patients with lung cancer diagnosis and use of anticoagulant/antiaggregant. In a study evaluating long-term prognostic outcomes in patients with hemoptysis, bronchiectasis was found to be associated with an increased risk of recurrence (19). Fidan et al and Ryuge et al also found bronchiectasis to be the most common diagnosis in recurrent hemoptysis (6,20).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, the most common recurrence risk was seen in patients with lung cancer diagnosis and use of anticoagulant/antiaggregant. In a study evaluating long-term prognostic outcomes in patients with hemoptysis, bronchiectasis was found to be associated with an increased risk of recurrence (19). Fidan et al and Ryuge et al also found bronchiectasis to be the most common diagnosis in recurrent hemoptysis (6,20).…”
Section: Resultsmentioning
confidence: 98%
“…However, in the correlation analysis, only the length of stay in the first hemoptysis was found to be associated with mortality. Mondoni et al reported that the overall mortality rate was 13.7%, increased from 18.1% to 31% after a one-year follow-up, and lung malignancy was the main determinant of mortality (19). Mortality rates are 50-100% in patients with massive hemoptysis treated conservatively (1).…”
Section: Resultsmentioning
confidence: 99%
“…A 2006 cohort study in Paris of 1087 individuals identified the most common causes of major hemoptysis as bronchitis (20%), cryptogenic (18%), cancer (17%), active tuberculosis (12%), and tuberculosis sequelae (13%) [ 2 ]. A report in 2018 of 606 patients with hemoptysis, showed malignancy (19%), pneumonia/lung abscess (19%), and bronchiectasis (15%) as the most common causes [ 3 ]. The cause of hemoptysis in our patient is exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…The United States Bronchiectasis Research Registry reported that 23% of patients with bronchiectasis had a history of hemoptysis [ 1 ]. The hemoptysis volume was larger than other diseases with more cases leading to recurrence [ 6 ]. In-hospital death rates due to hemoptysis among adults with bronchiectasis occurred in approximately 4.5–9.2% of hospitalizations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%